Junctophilins: Key Membrane Tethers in Muscles and Neurons - Piggott, Christopher A.; Jin, Yishi (Frontiers in Molecular Neuroscience, 2021)
Contacts between the endoplasmic reticulum (ER) and plasma membrane (PM) contain specialized tethering proteins that bind both ER and PM membranes. In excitable cells, ER–PM contacts play an important role in calcium signaling and transferring lipids. Junctophilins are a conserved family of ER–PM tethering proteins. They are predominantly expressed in muscles and neurons and known to simultaneously bind both ER- and PM-localized ion channels. Since their discovery two decades ago, functional studies using junctophilin-deficient animals have provided a deep understanding of their roles in muscles and neurons, including excitation-contraction coupling, store-operated calcium entry (SOCE), and afterhyperpolarization (AHP). In this review, we highlight key findings from mouse, fly, and worm that support evolutionary conservation of junctophilins.